Predictors of Poor Outcome of Anti-MDA5-Associated Rapidly Progressive Interstitial Lung Disease in a Chinese Cohort with Dermatomyositis - Yuhui Li; Yimin Li; Jian Wu; Miao Miao; Xiaojuan Gao; Wenxin Cai; Miao Shao; Xuewu Zhang; Yan Xu; Lu Cong; Jing He; Xiaolin Sun (Journal of Immunology Research)
Objective. Antimelanoma differentiation-associated protein 5 (anti-MDA5) autoantibody has been reported in dermatomyositis (DM) to be associated with rapidly progressive interstitial lung disease (RP-ILD). Our study is aimed at determining the clinical characteristics and prognostic factors underpinning anti-MDA5-associated RP-ILD. Methods. Patients with anti-MDA5-associated DM (aMDA5-DM) were identified at the Peking University People’s Hospital. The presence of anti-MDA5 antibody was determined by immunoblotting. Kaplan-Meier, chi-square test, univariate, and multivariate data analyses were used. Results. Out of 213 patients with DM and clinically amyopathic dermatomyositis (CADM), 20.7% (44/213) of patients were identified as aMDA5-DM. Amongst the aMDA5-DM patients, 63.6% (28/44) were identified as having anti-MDA5-associated RP-ILD. During the follow-up, 32.1% (9/28) of patients with anti-MDA5-associated RP-ILD died of respiratory failure. We identified older age and periungual erythema as two independent risk factors for RP-ILD mortality. Age≥57 years at disease onset was significantly associated with poor survival (P=0.02) in patients with anti-MDA5-associated RP-ILD, while patients with periungual erythema had a better survival rate than those without periungual erythema (P<0.05). Conclusions. Anti-MDA5-associated RP-ILD is significantly associated with poor survival rates in DM/CADM patients. More effective intervention should be administered to anti-MDA5-associated RP-ILD patients, especially to senior patients and those without periungual erythema.